The cost of implanting a cemented versus cementless total knee arthroplasty. (July 2019) - Lawrie, C. M.; Schwabe, M.; Pierce, A.; Nunley, R. M.; Barrack, R. L.
Abstract : Aims: The aim of this study was to compare the actual cost of a cemented and cementless total knee arthroplasty (TKA) procedure. Materials and Methods: The cost of operative time, implants, cement, and cementing accessories were included in the overall cost of the TKA procedure. Operative time was determined from a previously published study comparing cemented and cementless implants of the same design. The cost of operative time, implants, cement, and cementing accessories was determined from market and institutional data. Results: Mean operative time for cemented TKA was 11.6 minutes longer for cemented TKA than cementless TKA (93.7 minutes (sd 16.7) vs 82.1 minutes (sd 16.6); p = 0.001). Using a conservative published standard of 36 per minute for operating theatre time cost, the total time cost was 418 higher for cementing TKA. The cost of cement and accessories ranged from 170 to 625. Overall, the calculated cost of cemented TKA is 588 to 1043, depending on technique. The general increased charge for cementless TKA implants over cemented TKA implants was 366. Conclusion: The overall procedural cost of implanting a cementless TKA is less than implanting a cemented TKA. Cost alone should not be a barrier to using cementless TKA. Cite this article: Bone Joint J 2019;101-B(7 Supple C):61–63